2014
DOI: 10.3168/jds.2013-7428
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis toward carbohydrates and peptides by mixed ruminal protozoa when fed, fasted, or incubated with polyunsaturated fatty acids

Abstract: In contrast to the well-characterized chemotaxis and migratory behavior between the dorsal and ventral locations of the rumen by isotrichids, we hypothesized that chemotaxis toward soluble nutrients maintains entodiniomorphid protozoa in the particulate fraction. The objectives of these experiments were to compare the dose-responsive chemotaxis (1) toward different glucose concentrations when ruminal samples were harvested from fed versus fasted cows; (2) toward increasing concentrations of glucose compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
4
25
0
2
Order By: Relevance
“…A meta-analysis of S. cerevisiae supplementation indicated that it would increase protozoal growth (Desnoyers et al, 2009 ). Isotrichids have been shown to associate with plant particles due to chemotaxis toward a variety of sugars (Orpin and Letcher, 1978 ; Diaz et al, 2014a , b ), thus their increase in the present study with ADY treatment may result from the associated improvement in fiber digestion and availability of sugars (AlZahal et al, 2014 ).…”
Section: Discussionmentioning
confidence: 76%
“…A meta-analysis of S. cerevisiae supplementation indicated that it would increase protozoal growth (Desnoyers et al, 2009 ). Isotrichids have been shown to associate with plant particles due to chemotaxis toward a variety of sugars (Orpin and Letcher, 1978 ; Diaz et al, 2014a , b ), thus their increase in the present study with ADY treatment may result from the associated improvement in fiber digestion and availability of sugars (AlZahal et al, 2014 ).…”
Section: Discussionmentioning
confidence: 76%
“…It seems that the retention of ciliates in rumen is not similar for every protozoa group[8]. While Holotrichs have a strong chemotaxis toward sugars and after a meal migrate to the ventral reticulo-rumen, avoiding to be washed out, Entodiniomorphids have a moderate chemotaxis toward glucose and peptides and are uniformly distributed in ruminal content do not show the same affinity to the rumen wall as Holotrichs, and thus flow out of the rumen with the particulate matter [8, 45, 46]. The results of the present study are compatible with that dynamics of protozoa in rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Still, concentrations of Ïł5 mM can be reached after feeding unadapted animals large amounts of grain (6,30), and soluble sugar concentrations of 69 mM have been recorded after feeding beet pulp (31). Furthermore, concentrations of soluble sugars may be high around feed particles due to the accumulation of hydrolysis products from primary colonizers (28,32), and protozoa (both isotrichids and ophryoscolecids) display chemotaxis toward sugars (33). In our experiments, we intensified carbohydrate excess by removing N (by washing cells with N-free buffer).…”
Section: Discussionmentioning
confidence: 99%